High-performance reverse osmosis membranes fabricated on highly porous microstructured supports - Lee, Jaewoo (2018)
Increasing the surface porosity of a support membrane has been proposed as an effective way to improve the water permeability of thin-film composite (TFC) reverse osmosis (RO) membranes by reducing the diffusion pathway in the active layer. In this work, we prepared a highly porous microstructured (HPμS) support membrane with a suitable mechanical strength to enhance the water permeability of an RO membrane. The HPμS support membrane was prepared by increasing the thermodynamic instability of a 10 wt% polymer solution and thereby facilitating rapid desolvation. The rapid desolvation formed the narrow and regularly arranged pore structure in the sublayer, and we proposed the mechanism for the sublayer structure formation based on analyses of the thermodynamic properties of such a binary system. Owing to the narrow and regular structure, the HPμS support membranes showed the exceptional mechanical strength, which was comparable to the strength of support membranes used for conventional RO membranes. Also, the HPμS support membranes successfully endowed an in-house RO membrane with the performance (water permeability of 4.68 L m−2 h−1 bar−1 and NaCl rejection of 98.3%) surpassing commercial RO membranes and thin-film nanocomposite membranes recently reported in the literature.